ATTRACTING FOREIGN INVESTMENT IN THE AGRICULTURAL ECONOMY - Baxriddin Jurayevich, Mahmudov; Baxtiyarjon Bulturbayevich, Mullabayev (IJBLE Scientific Publications Community Inc., 2020)
The article discusses the importance of attracting domestic and foreign investments in the development of the agricultural economy, the experience of foreign countries and the problems of the analysis and investment of investment in fixed assets of agriculture in the Republic of Uzbekistan, as well as suggestions for their elimination.